Leadership in public administration: today's challenges - Shorobura, I.; Dolynska, O. (Journal of Education, Health and Sport, 2023)
The participation of the public in the formation and implementation of the state policy of promoting the development of civil society by the executive authorities is ensured. The issue of leadership in public administration is extremely relevant today. Leadership is the object of research by many scientists, three main theoretical approaches to understanding leadership (charismatic action, situational theory, synthetic theory) have been formulated. Leadership is a type of activity that permeates the entire management system. It is impossible to effectively perform the functions of planning, organization, motivation and control if there is no effective management and leaders. The manager’s personality is formed gradually. In psychology, various approaches to the development of theoretical models of personality development and the effectiveness of managerial activities of managers have been developed (collective approach, competitive, partial, engineering-psychological approach, reflective value approach, social-psychological, situational-complex approach, factor approach, functional approach, image approach, integrative). Seven skills and character traits of a manager valuable to companies are highlighted: leadership skills, strategic thinking, technical and technological skills, the ability to build relationships and create a team, the ability to present oneself and communicate, change management, honesty. The practice of training and retraining of managers includes active learning methods. The problem of the manager's culture in management philosophy is gaining importance. The main scientific disciplines are highlighted. Today, there are a significant number of grand programs for leaders of public administration that contribute to the development of leadership qualities. Self-management is the ability to manage oneself, one's potential, abilities, and knowledge. The working hours of the majority are condensed. The only solution can be the use of special techniques and methods, which have the general name of time management. There are many methods for solving problems related to the rational use of working time. The main principles of time management are highlighted.